Amyloid β (Aβ) inhibits retinal angiogenesis in Alzheimer's disease via LncRNA-XIST/miRNA-126-5p/VEGF axis - Bin Wang; Wenwei Li; Chaoyang Hong; Fangfang Jin; Baisheng Xu; Zhongwei Guo; Shuyang Chen; Qi Zhang (Immunobiology)
Alzheimer's disease (AD) is often accompanied by retinal lesions, in which Amyloid β (Aβ) is a key mediator. Vascular dysfunction is always associated with the malignant progression of AD, but the precise mechanisms remain poorly understood. The aim of this study is to investigate how Aβ regulates retinal angiogenesis in AD models through the LncRNA-XIST/miR-126-5p/VEGF axis. The research results showed that in the retina of AD model mice, the expression of Aβ and miR-126-5p increased, while the expression of LncRNA-XIST and VEGF decreased. In vitro experiments demonstrated that Aβ treatment downregulated LncRNA-XIST and VEGF expression in RF/6 A cells, while upregulating miR-126-5p and significantly suppressing angiogenesis. Overexpression of LncRNA-XIST can reverse the inhibitory effect of Aβ on angiogenesis, while further overexpression of miR-126-5p can counteract the pro-angiogenic effect of LncRNA-XIST. The dual-luciferase reporter assay results showed that Aβ repressed the transcriptional activity of the LncRNA-XIST promoter by targeting the −800 to −600 fragment. Mechanism studies have revealed that LncRNA-XIST competitively binds to miR-126-5p, preventing its binding to VEGF mRNA and upregulating VEGF expression. In vivo experiments demonstrated that miR-126-5p inhibitor resulted in elevated expression of LncRNA-XIST and VEGF in the mouse retina. This study reveals the molecular mechanism by which Aβ regulates retinal angiogenesis in AD models through the LncRNA-XIST/miR-126-5p/VEGF axis, providing a potential new strategy for targeted therapy of AD-related retinal lesions.